The role of satisfaction and trust in mobile CRM activities. (18th August 2008) - Lee, Dong-Il; Sohn, Changsoo; Lee, Hyejun
This study analysed customers' intention to continue to use mobile services as a way of mobile CRM activities. The analysed model explains that customers' intention is determined by trust. Trust is explained by satisfaction of mobile CRM activities, which is evaluated by contents differentiation, contact frequency, and contents repetition. Satisfaction is a significant predictor of intention without considering trust. However, when considering satisfaction and trust together, only trust explains customers' intention, but satisfaction does not directly explain customers' intention. This indicates that the effect of satisfaction on customers' intention is fully mediated by of trust. Thus, this study identified that customers' intention of continual usage can be achieved through trust. The result gives guidelines for mobile service providers to make customers have satisfaction and subsequently trust. Also, academically, it clarifies the relationship of trust and satisfaction in the context of mobile CRM activities.